2015
DOI: 10.1021/acs.est.5b02751
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biological Potency of Mono- to Tetra-Halogenated Carbazoles

Abstract: This paper deals with the characterization and aryl hydrocarbon receptor (AhR) agonist activities of a series of chlorinated, brominated, and mixed bromo/chlorocarbazoles, some of which have been identified in various environmental samples. Attention is directed here to the possibility that halogenated carbazoles may currently be emitted into the environment as a result of the production of carbazole-containing polymers present in a wide variety of electronic devices. We have found that any carbazole that is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 40 publications
0
38
1
Order By: Relevance
“…Therefore, the present study's results are consistent with the in vitro study in that all halogenated carbazoles were several orders of magnitude less potent than the dioxin analogue. It was also reported that only 2 lateral substituents (3 and 6) are necessary for high CYP1A induction for the chlorinated carbazoles . However, in our in vivo study, the 2 and 7 positions were necessary to become stronger CYP1A inducers.…”
Section: Resultscontrasting
confidence: 49%
See 2 more Smart Citations
“…Therefore, the present study's results are consistent with the in vitro study in that all halogenated carbazoles were several orders of magnitude less potent than the dioxin analogue. It was also reported that only 2 lateral substituents (3 and 6) are necessary for high CYP1A induction for the chlorinated carbazoles . However, in our in vivo study, the 2 and 7 positions were necessary to become stronger CYP1A inducers.…”
Section: Resultscontrasting
confidence: 49%
“…In 1 study, 3‐chlorocarbazole, 3,6‐dichlorocarbazole, and 36‐DBCZ were found to have dioxin‐like activity using ethoxyresorufin O ‐deethylase induction in rat hepatoma cells . In the other study, halogenated carbazoles showed structure‐dependent induction of cytochrome P450 (i.e., CYP1A and CYP1B) gene expression in aryl hydrocarbon–responsive MDA‐MB‐468 breast cancer cells, and the highest induction was similar to that observed for other dioxin‐like compounds . Therefore, it would be of great significance to investigate if those in vitro AhR‐mediated toxicities of polyhalogenated carbazoles could also be observed in an in vivo animal model.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, halogenation of carbazole is a key subject in medicinal chemistry and materials science and for this reason they are starting materials for the synthesis of numerous bioactive molecules of pharmaceutical importance despite their well-known toxicological characteristics [91]. These nitrogen containing heterocyclic compounds such as the mono-and polyhalogenated carbazoles (PHCZs) which are commonly known as nitrogenated dioxins are suggested to originate from either anthropogenic or natural sources and have been reported to possess toxicities comparable to those of dioxin and furan compounds basically because of their structural similarities [92]. From a chemical standpoint, the toxicity of polyhalogenated carbazoles (PHCZs) has been attributed to their resemblance with polychlorinated dibenzo-p-dioxin and dibenzofuran, with very close correlation between their planar molecular conformation and dioxin-like toxicological characteristics [23].…”
Section: Nitrogenated Analogues Of Dioxins Dibenzofurans and Their Cmentioning
confidence: 99%
“…It is important to note that halogenated carbazoles are structurally similar to polychlorinated dibenzo-p-dioxin and halogenated dibenzofurans; therefore they are believed to be extremely toxic because of their dioxin-like characteristic behaviour attributed to similarity in their molecular conformations [32]. Polyhalogenated carbazoles (PHCs) which has been established to be non-degradable in the soil [73] display toxicities similar to those of dioxins and furans and are precursors for carcinogenesis, developmental defects and lowered immunity in animals [92].…”
Section: Introductionmentioning
confidence: 99%